Answer:
- sequence 3
- no matching sequence
- no matching sequence
- no matching sequence
- sequence 2
- sequence 1
Explanation:
Recursively Defined Function Sequence
f(1) = 13 f(n) = f(n - 1) + 26 for n ≥ 2 13, 39, 65, 91, ...
f(1) = 13 f(n) = 3 · f(n - 1) for n ≥ 2
f(1) = -24 f(n) = -4 · f(n - 1) for n ≥ 2
f(1) = 28 f(n) = f(n - 1) - 84 for n ≥ 2
f(1) = 28 f(n) = -4 · f(n - 1) for n ≥ 2 28, -112, 448, -1,792, ...
f(1) = -24 f(n) = 4 · f(n - 1) for n ≥ 2 -24, -96, -384, -1,536, ...
__
The initial values are easily seen. They match f(1). The recursive functions can be tested to see if they match the offered sequences.
sequence 1 has a common ratio of 4 (not -4)
sequence 2 has a common ratio of -4 (it is not arithmetic)
sequence 3 has a common difference of 26 (it is not geometric)